Peningkatan Pengetahuan Calon Pengantin Melalui Konseling ASI Eksklusif di Kecamatan Darul Imarah Aceh Besar - Al-Rahmad, Agus Hendra (JURNAL NUTRISIA, 2017)
Background : Scaling Up Nutrition movement is a global effort to strengthen our commitment and accelerating action plan to improve nutrition, particularly the handling of nutrition in the first 1,000 days of life is exclusive breastfeeding and it until 24 months. One of the way is with exclusive breastfeeding counselling that can reduce stunting. The counseling is addressed to brides who need special attention in improving the nutrition and health. Objective : The aim of research to improve knowledge about exclusive breastfeeding counseling the bride through the use of leaflets. Method : This quasi-experimental study was a sample of 30 person a brides with non-random assignment, the variable a knowledge obtained through interviews using questionnaires while the method of counseling does face to face with an exclusive breastfeeding leaflet. The data was analyzed by dependent t-test. Result : The results showed exclusive breastfeeding counseling can improve knowledge bride (p= 0,000) with a mean difference is 6,13 and a deviation is 3,71. Conclusion : Increase of knowledge among ‘bride-to be’ about exclusive breastfeeding could be improved through the use of exclusive breastfeeding leaflet. Each health center must be in collaboration with Office of Religious Affairs to have exclusive breastfeeding counseling, and set one of the priority programs in the prevention of child stunting. Keywords: Bride, counseling, knowledge of exclusive breastfeeding